Beliefs Teacher on Improving Student’s English Writing Ability Through Digital Media - Lilik Uzlifatul Jannah; Suhartono Suhartono; Kisyani Kisyani; Syamsul Sodiq (International Journal of Science and Applied Science: Conference Series, 2022)
Teachers are role models for students. Its existence in the world of education cannot be denied. Good or bad Education is depend on this one figure. Teachers' beliefs form an understanding of how teachers learn to teach, creating meaningful learning for students as teachers. During the Covid-19 pandemic, the implementation of distance learning made students less enthusiastic and less understanding of the material and they often spent time with their gadgets. The importance of this research is to convince every educator that beliefs teacher is the right solution to improve students' English writing skills through digital media. The purpose of this study was to determine the effectiveness of teachers' beliefs in improving students' English writing skills through digital media. The research approach used is a quasi-experimental method. The sample for the survey consisted of 32 students of class 8B SMPN1 Kembangbahu. Research data were collected using (1) a questionnaire; (2) pre-test; (3) class treatment; and (4) post-test. Survey data analysis with ANOVA testing using SPSS. The test results will be displayed, whether it reaches the level of significance or not. The application of beliefs on students' English writing skills through digital media can (1) increase and attract students' interest in learning to write English. The test results will be displayed, whether it reaches the level of significance or not.